1998
DOI: 10.1083/jcb.141.3.805
|View full text |Cite
|
Sign up to set email alerts
|

PDGF, TGF-β, and Heterotypic Cell–Cell Interactions Mediate Endothelial Cell–induced Recruitment of 10T1/2 Cells and Their Differentiation to a Smooth Muscle Fate

Abstract: We aimed to determine if and how endothelial cells (EC) recruit precursors of smooth muscle cells and pericytes and induce their differentiation during vessel formation. Multipotent embryonic 10T1/2 cells were used as presumptive mural cell precursors. In an under-agarose coculture, EC induced migration of 10T1/2 cells via platelet-derived growth factor BB. 10T1/2 cells in coculture with EC changed from polygonal to spindle-shaped, reminiscent of smooth muscle cells in culture. Immunohistochemical and Western … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
661
1
2

Year Published

2000
2000
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 753 publications
(687 citation statements)
references
References 68 publications
23
661
1
2
Order By: Relevance
“…In the meantime, the recruitment of SMCs is vital to stabilize the newly formed endothelium 32, 39, 40, 41, 42. In this study, we have demonstrated that the inclusion of 7A, especially the phosphorylated version 7Ap, significantly increased endothelialization.…”
Section: Discussionmentioning
confidence: 53%
“…In the meantime, the recruitment of SMCs is vital to stabilize the newly formed endothelium 32, 39, 40, 41, 42. In this study, we have demonstrated that the inclusion of 7A, especially the phosphorylated version 7Ap, significantly increased endothelialization.…”
Section: Discussionmentioning
confidence: 53%
“…We previously demonstrated that the C3H10T1/2 cell system represents a highly useful cell culture model for studying effects of Msx2 on osteogenic, adipogenic, and smooth muscle differentiation (10). This mesenchymal progenitor shares features of vascular myofibroblasts and can readily adopt the mural VSMC fate when transplanted in vivo (30). Therefore, we assessed whether the conditioned media (CM) from Msx2-transduced 10T1/2 cells could alter osteogenic and/or adipogenic differentiation.…”
Section: Cmv-msx2 Transgenic Mice Exhibit Cardiovascular Calcificatiomentioning
confidence: 99%
“…Mural cells, including vascular smooth muscle cells and pericytes, together with endothelial cells, possess the potential of recruiting cells from the surrounding tissue in vivo [12]. MSCs can be differentiated into both endothelial and mural cells in vitro and in vivo [13]. Our preliminary studies demonstrated that endothelial cells seeded into the vasculature of the ECM were only shown to survive and reach a stabilized phase over time without Endothelialization of Acellular Porcine ECM with Chemical Modification proliferation, which is necessary for the formation of functional blood vessels.…”
Section: Introductionmentioning
confidence: 99%